Transtornos mentais comuns e fatores associados entre mulheres privadas de liberdade no Brasil - Menezes, Francisco Wagner Pereira (2023)
Several countries have gradually consolidated a penal state that contributes to the escalation of incarceration. In the Brazilian case, the growth in the number of women deprived of their liberty stands out, with an increase of 442% between the years 2000 and 2016. It is observed that the burden of diseases and other adverse health events is greater among these in compared to male prisoners and female members of the general population. This study aimed to characterize the prevalence of Common Mental Disorders (CMD) among Brazilian women deprived of liberty and its associated factors. This is a cross-sectional study, constituting a part of the research “National Health Survey in the Female Penitentiary Population and Prison Servants”. The sampling process was carried out in 5 stages: survey of female prisons in Brazil; stratification of prisons; random choice of a prison in each stratum; sample size calculation considering the prevalence of Sexually Transmitted Infection; and random selection of women in each penitentiary. The final sample collected was 1.327 women. A respondent with a score ≥ 7 on the Self Report Questionnaire-20 (SRQ-20) was considered a case of CMD. The independent variables comprise 5 categories: socioeconomic and demographic; health conditions; use of alcohol and other drugs; prison factors and violence. The prevalence of CMD was 64.3% (95% CI: 61.5 – 66.9). The factors associated with the highest prevalence were: less education (complete/incomplete elementary school: OR = 1.78; 95% CI: 1.14 – 2.76), working before prison (OR = 1.62; 95% CI: : 1.07 – 2.44), having had a teenage pregnancy (OR = 1.56; 95% CI: 1.09 – 2.22); having been homeless (OR = 1.72; 95% CI: 1.00 – 2.94); having high blood pressure (OR = 1.90; 95% CI: 1.23 – 2.94), having an asthma attack or chronic bronchitis (OR = 1.87; 95% CI: 1.16 – 2.99), having or having had an STI (OR = 1.41; 95% CI: 1.01 – 1.98); having a poor perception of their health (OR = 3.21; 95% CI: 2.56 – 4.29); having used tranquilizers in life (OR = 1.90; 95% CI: 1.23 – 2.94); perform insufficient physical activity in prison (OR = 2.04; 95% CI: 1.22 – 3.42); having been placed in isolation (OR = 1.82; 95% CI 1.21 – 2.75). Finally, as factors linked to violence, having suffered or witnessed violence in prison (OR = 1.87; 95% CI 1.30 – 2.69). It is concluded from the results obtained that the high prevalence of CMD among women deprived of their liberty in Brazil corroborates the existence of multiple overlapping risk factors, urging their consideration in the formulation of policies and humanized care strategies for this marginalized population. even before arrest.